HARD SKILLS MATEMATIK SISWA: PENGERTIAN DAN INDIKATORNYA - Darwanto Darwanto (Universitas Muhammadiyah Kotabumi, 2019)
Education curriculum in Indonesia focuses on the ability of hard skills and soft skills. Both of these capabilities must be synergized and balanced in their implementation in realizing learning goals and also curriculum objectives. Hard skills have several types, namely: mathematical understanding, mathematical reasoning, mathematical problem solving, mathematical communication, mathematical connections, mathematical logical thinking, mathematical critical thinking, and mathematical creative thinking. Each of these types has an indicator so that learning objectives are achieved.